Kinerja Keuangan PT Bank Syariah Indonesia dan Kaitannya dengan Pertumbuhan Ekonomi Indonesia - Faradilla, Ananda Natasya; Astuty, Sri; Kamaruddin, Citra Ayni; Rajab, Abdul; Regina, Regina (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
The development of Islamic banking in Indonesia following the merger has positioned PT Bank Syariah Indonesia (BSI) as a strategic entity within the national financial system. In line with this role, it is important to understand how BSI’s financial performance has evolved and how it is empirically related to Indonesia’s economic growth. This study aims to provide an empirical overview of the financial performance of PT Bank Syariah Indonesia and its descriptive association with Indonesia’s economic growth during the 2019–2023 period. This study employs a descriptive quantitative approach with a non-experimental research design. The data used are secondary data obtained from the annual financial reports of PT Bank Syariah Indonesia and Indonesia’s Gross Domestic Product (GDP) data. The bank’s financial performance is measured using Return on Assets (ROA), Return on Equity (ROE), and Capital Adequacy Ratio (CAR), while economic growth is proxied by GDP. The analytical methods applied include descriptive analysis and trend analysis to identify patterns and dynamics in the observed variables over the study period. The results indicate that PT Bank Syariah Indonesia’s financial performance experienced varying dynamics, with improvements observed in certain profitability and capital adequacy indicators during specific periods. Descriptively, the movement of BSI’s financial performance tends to align with the dynamics of Indonesia’s economic growth. However, this association is not intended to imply a causal relationship, but rather to represent an initial and contextual empirical indication.